Development and characterization of sodium tripolyphosphate cross-linked chitosan/guar gum composite films reinforced with bentonite clay for food packaging application - Aminu Abdullahi; Tarangini Korumilli; K. Jagajjanani Rao (Next Materials, 2025)
The increasing demand for sustainable food packaging materials has driven research into natural polymer based films as alternatives to conventional plastics. This work reported a novel STPP cross-linked composite film based Chitosan/Guar gum reinforced with Bentonite clay. The biopolymer composite films were prepared by solvent casting methods using chitosan 1 % (w/v), guar gum 1.5 % (w/v), STPP 0.09 % (w/v), glycerol 2 % (w/v) with addition of varying concentration of bentonite clay (0.05 %. 0.1 %, 0.25 % and 0.4 % w/v). The cross-linking effect and evidence of components interactions has been confirmed by Fourier transform infrared (FTIR) analysis. The addition of bentonite clay (BT) to chitosan/guar gum (CS/GG) films markedly improves hydrophobicity, water resistance (reduced swelling and solubility) and barrier properties (WVTR). The films with 0.25, and 0.1 % BT reinforcement shows highest water repellence capacity with water contact angle (WCA) values of 111˚ and 106.75˚ respectively. Furthermore, film containing 0.25 % BT concentration is the most effective in enhancing mechanical and barrier properties compared to control and all other films attributable to its crystalline structure as evident in XRD patterns. The films displayed significant antimicrobial efficacy against bacteria gram-positive (Bacillus cereus and Staphylococci aureus), gram-negative (Escherichia coli) and fungal F. oxysporum. In addition, notable antioxidant activity against of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals with highest quenching activity of 87.39 ± 0.01 % was observed in CS/GG/0.4 %(w/v) BT film, followed by CS/GG/0.25 % (w/v) BT film (87.12 ± 0.2 %). The study also underscores the potential of STPP as a crosslinking agent and bentonite filler for the development of composite film, suggesting applications in food packaging.